1976
DOI: 10.1016/s0022-5347(17)59220-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced Carcinoma of the Prostate with Estramustine Phosphate

Abstract: Estramustine phosphate has been useful in the treatment of advanced carcinoma of the prostate. Objective remissions were obtained with this therapy in 6 of 17 patients (35 per cent). The results presented herein indicate that the clinical response is to a certain extent caused by an estrogen effect, which was clearly demonstrable in a previously untreated patient. A specific cytostatic effect of estramustine phosphate, which is not yet clearly explained, may be responsible for remissions in some patients who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Estramustine was one of the first effective chemotherapeutics shown to improve biochemical response in mCRPC, but also has anti‐androgen effects due to the oestradiol component. However, gastrointestinal and thromboembolic toxicities have resulted in estramustine being rarely administered . Older agents, such as platinums, cyclophosphamide and 5‐fluorouracil, demonstrate marginal single‐agent activity using suboptimal response criteria in an unselected group of men with prostate cancer and have not been further developed partly due to lack of commercial incentives .…”
Section: Conventional Chemotherapy Regimens For Mcrpcmentioning
confidence: 99%
“…Estramustine was one of the first effective chemotherapeutics shown to improve biochemical response in mCRPC, but also has anti‐androgen effects due to the oestradiol component. However, gastrointestinal and thromboembolic toxicities have resulted in estramustine being rarely administered . Older agents, such as platinums, cyclophosphamide and 5‐fluorouracil, demonstrate marginal single‐agent activity using suboptimal response criteria in an unselected group of men with prostate cancer and have not been further developed partly due to lack of commercial incentives .…”
Section: Conventional Chemotherapy Regimens For Mcrpcmentioning
confidence: 99%
“…It has been suggested that the steroid fraction acts as a carrier to hormone-dependent tumour tissue where the alkylating agent is released and exerts a direct action (Muntzing et al, 1974). Earlier reports showed an encouraging response in advanced disease (Alfthan and Rusk, 1969;Jonsson and Hogberg, 1971) and subsequent reports have continued to show a useful clinical response (Fossa and Miller, 1976;Mittleman, Shukla and Murphy, 1976;Nagel and Kolln, 1977).…”
mentioning
confidence: 98%
“…Also estramustine phosphate represents a high-dose estrogen treatment and acts probably also as a cytostatic agent. The drug has been shown to relieve pain and to improve the general condition in prostate cancer patients who progress on ongoing primary hormone manipula tions [21,22], According to the present study with admittedly few patients within each group, secondary hormone treatment with 1 of the above 3 hormonal agents reduces elevated PSA levels by > 50% in 20-30% of the patients with hor mone-resistant prostate cancer. These biochemical re sponses objectively indicate that at least some of the tumor cells are still sensitive for endocrine manipulation.…”
Section: Treatmentmentioning
confidence: 57%